2020
DOI: 10.1186/s12302-020-00379-6
|View full text |Cite
|
Sign up to set email alerts
|

Stacked genetically modified soybean harboring herbicide resistance and insecticide rCry1Ac shows strong defense and redox homeostasis disturbance after glyphosate-based herbicide application

Abstract: Background World agricultural production of genetically modified (GM) products, in particular, the combination of different traits/genes in the same plant has been a trend over the last decade. There have been concerns raised over stacking multiple herbicide and insect-resistant transgenes that could result in fitness costs depending on the type and strength of selection pressures exerted by the environment. Here, we report the results of transcriptomic analysis comparing the effect of glyphosate-based herbici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 97 publications
(121 reference statements)
2
21
0
1
Order By: Relevance
“…The synthesis of several natural products, including pigments and hormones, directly requires intermediates from the shikimate pathway (Maeda & Dudareva, 2012); similar to Zanatta et al, (2020), we find that genes functioning in response to chemicals are involved in diverse regulation of auxin, ethylene, abscisic acid, jasmonic acid and gibberellin. Since glyphosate accumulation occurs in active metabolic tissues (Cakmak et al, 2009), the primary location of plant hormone production, part of the toxicity induced by glyphosate is known to be the hormonal imbalance that influences both growth and development (Gomes et al, 2014).…”
Section: Candidate Genesmentioning
confidence: 75%
See 3 more Smart Citations
“…The synthesis of several natural products, including pigments and hormones, directly requires intermediates from the shikimate pathway (Maeda & Dudareva, 2012); similar to Zanatta et al, (2020), we find that genes functioning in response to chemicals are involved in diverse regulation of auxin, ethylene, abscisic acid, jasmonic acid and gibberellin. Since glyphosate accumulation occurs in active metabolic tissues (Cakmak et al, 2009), the primary location of plant hormone production, part of the toxicity induced by glyphosate is known to be the hormonal imbalance that influences both growth and development (Gomes et al, 2014).…”
Section: Candidate Genesmentioning
confidence: 75%
“…The KEGG pathways in soybean with the largest number of genes involved in response to glyphosate were metabolic pathways and biosynthesis of secondary metabolites (Zanatta et al, 2020). In comparison, of our six GO categories that were significant even after conservative Bonferroni correction, four were related to metabolism or biosynthesis.…”
Section: Candidate Genesmentioning
confidence: 79%
See 2 more Smart Citations
“…Profiling techniques are broadly accepted as being capable of delivering sound descriptions of their target class of molecule in a range of diverse field from molecular medicine to food safety and plant physiology studies (Karahalil, 2016;Argueso et al, 2019;Mehta et al, 2019;Carrera et al, 2020). A number of molecular profiling studies have already indicated unintended effects of genetic modification (Coll et al, 2011;Wang et al, 2015Wang et al, , 2019Zanatta et al, 2020). These studies revealed inter alia that compared to an effect of the genetic modification in the GM plants, there is also effects on the plant's physiology arising from (i) the genetic background, (ii) environmental conditions during growth, (iii) sampling procedures and (iv) plant-to-plant variability.…”
Section: Suitability and Reproducibility Of 2-d Gel-based Dige Experimentsmentioning
confidence: 99%